Treatment Patterns in Essential Tremor: A Retrospective Analysis. Issue 1 (23rd March 2022) - Shah, Chintan; Jackson, George R.; Sarwar, Aliya I.; Mandava, Pitchaiah; Jamal, Fariha
Background: Although first line therapies for essential tremor have been identified from small clinical trials, responses are variable. We conducted a survey of tremor management in a large sample of ET cases. Methods: The Movement Disorders Clinical Case Registry within a US Veterans Health Administration medical center was used to identify 1468 patients with ET. Results: Of 1468 charts reviewed, 1074 (73.19%) met criteria for ET with characterization of temporal course and treatment; 291/1074 subjects (27.1%) did not receive any treatment. Almost half (500/1074; 46.6%) of the patients received monotherapy, 196/1074 (18.2%) two, 66/1074 (6.1%) three, and 21/1074 (2.0%) four or more medications. Of all prescriptions, primidone was the most used (546/1172; 46.6%), followed by propranolol (419; 35.8%), topiramate (122; 10.4%) and gabapentin (35; 3.0%). Medication response was available for a total of 1030 prescriptions, of which 138 (13.4%) were discontinued due to side effects; 180 (17.5%) prescriptions were ineffective. Furthermore, 52/1074 patients (4.8%) were treated with botulinum toxin injections and 41/1074 (3.8%) underwent deep brain stimulation surgery. Discussion: Our data suggest that more widespread recognition of limitations underlying conventional approaches, as well as increased referrals for nonpharmacological therapies, may be necessary to achieve improved outcomes in ET populations.